Termination of the lease: certain legal aspects - Паскевич, Юлія Владиславівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals with questions that are related to features of the termination of lease contract as a result of its cancellation and investigates the specific features of individual cases of contract cancellations. The article is based on the analysis of national legislation that regulates the grounds, procedure and consequences of the contract cancellation and includes analysis of positions of Ukrainian and foreign scientists.